Severe Hemorrhage from the Umbilical Cord at Birth: A Preventable Cause of Neonatal Shock. (4th November 2013) - Singh, Neetu; Suresh, Gautham
Abstract : Posthemorrhagic anemia is a rare but important cause of anemia in neonates, second only to hemolytic anemia of newborn. Most cases of posthemorrhagic anemia are reported from fetomaternal hemorrhage or umbilical cord accidents in utero. This case report describes a preterm infant who developed severe anemia and shock immediately after delivery related to an acute hemorrhage through patent umbilical cord vessels secondary to a tear in the umbilical cord at the site of cord clamping. We believe that umbilical cord bleeding from errors in cord clamping could be an important cause of acute blood loss in the delivery room and that it may result in significant clinical morbidity, especially in extremely premature infants.